Recovery of coral cover at Lizard island Australia 6 years post-disturbance - Gabriel Dax Anderson (Frontiers in Marine Science)
Coral reefs are experiencing more intense and frequent disturbances induced by climate change, such as cyclones and bleaching events. This necessitates a better understanding of the ongoing environmental conditions that stress these systems and the subsequent arc of longer-term reef responses to these stressful conditions. From March of 2014 to May of 2017, the Lizard Island reefs in the northern region of the Great Barrier Reef experienced four consecutive annual disturbances; Cyclone Ita in 2014, Cyclone Nathan in 2015, and two massive bleaching events in 2016 and 2017. Between the concentrated patches of physical damage from the cyclones and the uniform impact of the bleaching events, these reefs were devastated, with none of the eight study sites harboring more than 20% live coral cover by May of 2017. In November of 2023, after six years of relatively calmer conditions with no conspicuous region-wide, large-scale disturbances, I documented the extant coral community on eight previously-monitored reefs around Lizard Island. All reefs showed significant (p = 0.0054, F = 3.46, df = 47) improvement from their 2017 immediate post-disturbance degradation. Living coral at my study sites had recovered to between 18.4 ± 0.6 (mean ± 1 SE) to 59.9 ± 5.3% of the reef area per site by 2023, with many sites towards the higher end of that range. Recovery of coral extent appeared to follow a north-south trend in which more Trade Wind-sheltered northerly sites had generally greater recovery and higher live coral cover compared to more exposed southern sites, which experienced significantly less coral recovery. Fast-growing Acroporid corals drove the recovery of coral extent in these more northern sites. While family richness across all sites improved by 2023 (4.0 ± 0.1; grand mean ± 1 se), Lizard Island reefs have yet to reach their pre-disturbance diversity (4.8 ± 0.6 in 2014). Future annual surveys of the study sites as well as others surveyed in 2017 may better clarify the relationship between reef location and the rate of recovery of coral cover post-disturbance.